2012
DOI: 10.3892/mmr.2012.960
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of lipopolysaccharide-induced upregulation of toll-like receptor 4 by emodin in mouse proximal tubular epithelial cells

Abstract: The aim of this study was to investigate the effects of emodin, the major component of Rheum palmatum, on lipopolysaccharide (LPS)-induced toll-like receptor 4 (TLR4) expression in cultured mouse tubular epithelial cells (TECs). The TECs were obtained from mice and incubated with LPS and/or indicated concentrations of emodin for 24 h. Cytokeratin, α-SMA and vimentin were detected using immunohistochemistry. The TLR4 protein level was detected by flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…The effect of LPS on TLR4 expression has been the object of conflicting results (Bosisio et al, ). While in some cases it was found to up‐regulate TLR4 (Muzio et al, ; Visintin et al, ; Zhu et al, ) other studies showed that LPS decreased or did not change TLR4 levels (Medvedev et al, ; Nomura et al, ). This alternating effect of LPS on TLR4 expression can be attributed to its' differential effect in different organs (Matsumura et al, ) and a result of different concentrations and time exposures protocols (Muzio et al, ; Nomura et al, ; Visintin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of LPS on TLR4 expression has been the object of conflicting results (Bosisio et al, ). While in some cases it was found to up‐regulate TLR4 (Muzio et al, ; Visintin et al, ; Zhu et al, ) other studies showed that LPS decreased or did not change TLR4 levels (Medvedev et al, ; Nomura et al, ). This alternating effect of LPS on TLR4 expression can be attributed to its' differential effect in different organs (Matsumura et al, ) and a result of different concentrations and time exposures protocols (Muzio et al, ; Nomura et al, ; Visintin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased TLRs, such as TLR-4, has been detected in circulating monocytes of patients with IgAN [ 31 ]. Expression of IL6 protein is also increased in mouse proximal tubular epithelial cells, accompanying by the upregulation of TLR4 mRNA [ 32 ]. IL1B, encoded by IL1B gene, is a member of interleukin 1 cytokine family and crucial for the regulation of inflammatory response [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] As the main active ingredient of rhubarb, emodin regulates lipopolysaccharide-induced toll-like receptor 4 and reduces the expression of tumor necrosis factor alpha and interleukin 6, all three being synthesized by renal tubular epithelial cells. [ 22 ] Emodin also acts as an anti-inflammatory agent by inhibiting the differentiation and maturation of dendritic cells and increasing the number of regulatory T-cells. [ 23 ] Astragaloside is a main active ingredient in traditional Chinese medicine and acts both as an anti-inflammatory and antifibrotic agent,[ 24 25 ] while salvianolic acid A has been shown to have cardiovascular protective effects.…”
Section: Discussionmentioning
confidence: 99%